Nonadministration of medication doses for venous thromboembolism prophylaxis in a cohort of hospitalized patients. (15th March 2018) - Popoola, Victor O.; Lau, Brandyn D.; Tan, Esther; Shaffer, Dauryne L.; Kraus, Peggy S.; Farrow, Norma E.; Hobson, Deborah B.; Aboagye, Jonathan K.; Streiff, Michael B.; Haut, Elliott R.
Abstract : Purpose: Results of a study to characterize patterns of nonadministration of medication doses for venous thromboembolism (VTE) prevention among hospitalized patients are presented. Methods: The electronic records of all patients admitted to 4 floors of a medical center during a 1-month period were examined to identify patients whose records indicated at least 1 nonadministered dose of medication for VTE prophylaxis. Proportions of nonadministered doses by medication type, intended route of administration, and VTE risk categorization were compared; reasons for nonadministration were evaluated. Results: Overall, 12.7% of all medication doses prescribed to patients in the study cohort ( n = 75) during the study period (857 of 6, 758 doses in total) were not administered. Nonadministration of 1 or more doses of VTE prophylaxis medication was nearly twice as likely for subcutaneous anticoagulants than for all other medication types (231 of 1, 112 doses [20.8%] versus 626 of 5, 646 doses [11.2%], p < 0.001). For all medications prescribed, the most common reason for nonadministration was patient refusal (559 of 857 doses [65.2%]); the refusal rate was higher for subcutaneous anticoagulants than for all other medication categories (82.7% versus 58.8%, p < 0.001). Doses of antiretrovirals, immunosuppressives, antihypertensives, psychiatric medications, analgesics, and antiepileptics were less commonly missed than doses of electrolytes, vitamins, and gastrointestinal medications. Conclusion: Scheduled doses of subcutaneous anticoagulants for hospitalized patients were more likely to be missed than doses of all other medication types.